2018
DOI: 10.3855/jidc.10081
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of biosafety measures in clinical laboratories of Al-Madinah city, Saudi Arabia

Abstract: Introduction: Workers in clinical laboratories are exposed to occupational hazards on a daily basis and their health and safety may be threatened if appropriate protective standards are not implemented. The aim of this study was to assess the knowledge and practices of clinical laboratory workers towards biosafety measures, in Al-Madinah city, Saudi Arabia. Methodology: Clinical laboratory staff was recruited from both the public and private sectors. A structured self-administered questionnaire was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
(36 reference statements)
3
6
0
Order By: Relevance
“…The current findings revealed that more than one third of the lab worked did not attend safety training or orientation programs. Another study from Al Madinah, Saudi Arabia, (35) showed that a fraction of medical laboratory staff participated in the study had no previous training on lab safety, which is almost similar to ours, and this was associated with inappropriate behaviors like use of cosmetics, eating/drinking in the labs, and continue working with torn gloves and injured fingers. The percentage of those who did not receive training is considered low when compared to equivalent regional studies.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The current findings revealed that more than one third of the lab worked did not attend safety training or orientation programs. Another study from Al Madinah, Saudi Arabia, (35) showed that a fraction of medical laboratory staff participated in the study had no previous training on lab safety, which is almost similar to ours, and this was associated with inappropriate behaviors like use of cosmetics, eating/drinking in the labs, and continue working with torn gloves and injured fingers. The percentage of those who did not receive training is considered low when compared to equivalent regional studies.…”
Section: Discussionsupporting
confidence: 69%
“…almost 18 % reported that they continued working with a finger cut, whereas only 67% reported that they used to recap needles after blood withdrawal. (35) In Philippines high institutions (36) , and in others study (37) , absence of safety data sheets (SDS) of chemicals and apparatuses, absence of complete personal protective equipment (PPE) absence of safety cabinets for chemicals storage were recorded respectively. The main goal of the study was to assess the level of occupational safety practices among laboratory staff in governmental hospitals in Riyadh, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, 13 (8.6%) have no training course. These results are consistent with the study findings conducted in Al-Madinah city, Saudi Arabia [6], which found that the majority of the workers in the laboratory were trained in laboratory safety. improving the retention of health professionals' training and specialist training courses has a positive impact on a range of important health indicators.…”
Section: Discussionsupporting
confidence: 92%
“…Table (5) shows that the overall assessment of COVID-19 measures has a good assessment score (4.02±0.43) with an answer rate of 80.4%. Table (6) shows that there is no significant association between the overall assessment score of employees and demographic characteristics (P. value >0.05), except for age groups have a significant association with the overall assessment score of employees at a significant level <0.05, age group 40-49 have a good assessment score.…”
Section: 4% Acceptablementioning
confidence: 91%
“…5 A variety of studies have been conducted worldwide, including the Middle East, to assess safety practices in chemistry, biology, and medical laboratories, in academic institutions and other health workplaces. [6][7][8][9][10][11] These studies indicate a lack of knowledge, and a misunderstanding of safety concepts, placing emphasis on increasing safety awareness through lectures, training, and other activities. Some studies recommend further in-depth research, with larger sample sizes, to collect more data to resolve this critical issue, 12 or to introduce safety education as an integral part of academic curricula.…”
Section: Introductionmentioning
confidence: 99%